Composite material, bolometer, and method for forming composite material

A composite material with oxide particles and carbon nanotubes, modified with a silane coupling agent, addresses the challenge of network formation in bolometers, resulting in a three-dimensional network structure that enhances sensor performance by reducing resistance and increasing conductive paths.

JP2024178094APending Publication Date: 2024-12-24NEC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024028280
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2024-02-28
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing bolometer materials face challenges in forming a network of carbon nanotubes when combining semiconducting carbon nanotubes with negative thermal expansion materials, leading to difficulties in network structure formation.

Method used

A composite material is developed comprising oxide particles with a specific particle size and carbon nanotubes, where the oxide particles are modified with a silane coupling agent to facilitate the formation of a three-dimensional network structure by dispersing carbon nanotubes on their surface.

Benefits of technology

The composite material easily forms a network of carbon nanotubes, increasing the number of conductive paths and reducing resistance, thereby enhancing the sensitivity and performance of infrared sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178094000001_ABST
    Figure 2024178094000001_ABST
Patent Text Reader

Abstract

To provide a composite material, a bolometer, and a method for forming a composite material that makes it easy to form a carbon nanotube network.SOLUTION: A composite material includes a film containing oxide particles having a particle size of at least 0.4 μm or more, and carbon nanotubes that form a network on the surface of the oxide particles.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to composite materials, bolometers, and methods of forming composite materials. [Background technology]

[0002] The use of carbon nanotubes in infrared sensors, including bolometers, is known.

[0003] For example, Patent Document 1 discloses the application of a thin film in which a semiconducting carbon nanotube and a negative thermal expansion material are mixed to a bolometer material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2021 / 241575 Summary of the Invention [Problem to be solved by the invention]

[0005] The bolometer material disclosed in Patent Document 1 may have difficulty in forming a network of carbon nanotubes when forming a thin film in which semiconducting carbon nanotubes and a negative thermal expansion material are mixed.

[0006] An object of the present disclosure is to provide a composite material, a bolometer, and a method for forming a composite material that solves the above-mentioned problems. [Means for solving the problem]

[0007] A composite material according to one embodiment of the present disclosure includes a film containing oxide particles having a particle diameter of at least 0.4 μm or more, and carbon nanotubes forming a network on the surfaces of the oxide particles.

[0008] A composite material forming method according to one embodiment of the present disclosure includes the steps of preparing a solution containing a silane coupling agent, adding a powder of oxide particles to the solution to prepare a first suspension, preparing a second suspension containing carbon nanotubes, preparing a third suspension containing the carbon nanotubes and the powder, and dropping the third suspension to form a film containing oxide particles having a particle diameter of at least 0.4 μm or more.

[0009] A composite material forming method according to one embodiment of the present disclosure includes the steps of: dripping a suspension containing oxide particles having a particle size of at least 0.4 μm or more and drying to form a porous film containing the oxide particles; and impregnating the porous film with a suspension containing carbon nanotubes. Effect of the Invention

[0010] According to the above aspect, a network of carbon nanotubes can be easily formed. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a side view of the composite material according to the first embodiment. [Diagram 2] 1 is a flowchart of a method for forming a composite material in a first embodiment. [Diagram 3] FIG. 1 is a diagram I showing the forming procedure of the composite material forming method in the first embodiment. [Figure 4] FIG. II shows the forming procedure of the composite material forming method in the first embodiment. [Diagram 5] FIG. 11 is a side view of a bolometer according to the second embodiment. [Figure 6] FIG. 13 is a side view of a minimum configuration of a composite material in the third embodiment. [Figure 7] 13 is a flowchart of a minimum configuration of a composite material forming method in a fourth embodiment. [Figure 8] 13 is a flowchart of a method for forming a composite material in a fifth embodiment. [Figure 9] FIG. 13 is a side view I of a porous membrane in the fifth embodiment. [Figure 10] FIG. 2 is a side view II of a porous membrane in the fifth embodiment. [Figure 11] FIG. 13 is a side view of a composite material in a fifth embodiment. [Figure 12] 13 is a flowchart of a minimum configuration of a composite material forming method in a sixth embodiment. [Figure 13] FIG. 2 is a plan view of a test element in an example. [Figure 14] FIG. 2 is a cross-sectional view of a test element in an example. [Figure 15] 1 is a graph showing the IV measurement results when the ambient temperature of a test element in an example is 293 K. [Figure 16] 1 is a graph showing the IV measurement results when the ambient temperature of a test element in an example is 313 K. [Figure 17] 1 is a graph showing the relationship between the average resistance value and the temperature coefficient of resistance of a test element in an embodiment. [Figure 18] 1 is a SEM image showing the adhesion state of a test element in an example. [Figure 19] 1 is a SEM image showing the adhesion state of a test element in an example. [Figure 20] 1 is a SEM image showing the adhesion state of a test element in an example. [Figure 21] 1 is a SEM image showing the adhesion state of a test element in an example. [Figure 22] 1 is a SEM image showing the adhesion state of a test element in an example. [Figure 23] FIG. 2 is a side view of a test element in an embodiment. [Figure 24] 11 is a SEM image showing the adhesion state of a test element in Example 2. [Diagram 25] 11 is a graph showing the relationship between the resistance value and the temperature coefficient of resistance of a test element in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, each embodiment of the present disclosure will be described with reference to the drawings. Note that the drawings and specific configurations used in each embodiment should not be used to interpret the disclosure. The same or corresponding configurations in all drawings are given the same reference numerals, and common descriptions are omitted.

[0013] First Embodiment A first embodiment according to the present disclosure will be described below with reference to FIGS. 1 to 4. FIG.

[0014] (Composition of composite materials) As shown in FIGS. 1 and 2, the composite material 1 includes a film 10 and carbon nanotubes 20. For example, the composite material 1 has a temperature coefficient of resistance that exhibits a negative value. For example, the composite material 1 has a temperature coefficient of resistance whose absolute value is 2.5% / K or more, and the temperature coefficient of resistance in the composite material 1 is a value when the ambient temperature is changed from 20°C to 25°C. For example, Composite Material 1 has a sheet resistance of 30 MΩ or less at an ambient temperature of 20°C. The thickness of the composite material 1 can be appropriately set. For example, the thickness of the composite material 1 is 2 μm to 6 μm. The film 10 includes oxide particles 101 . For example, the oxide particles 101 may have a particulate form. The particle diameter of the oxide particle 101 may be approximately the same as the length of the carbon nanotube 20 . The larger the particle diameter of the oxide particles 101, the easier it is for the long carbon nanotubes 20 to form a three-dimensional structure. The smaller the particle diameter of the oxide particles 101, the easier it is for the carbon nanotubes 20, which have a short length, to form a three-dimensional structure. For example, the oxide particles 101 have a particle diameter of at least 0.4 μm in the microscopic image described later. For example, the oxide particles 101 may have a particle diameter of 0.4 μm or more and 1.5 μm or less. For example, the oxide particles 101 may have a particle diameter of 0.5 μm or more and 1.5 μm or less. For example, the oxide particles 101 may have a particle diameter of 0.6 μm or more and 1.5 μm or less. For example, the oxide particles 101 may have a particle diameter of 0.7 μm or more and 1.5 μm or less. For example, the oxide particles 101 may have a particle diameter of 1.2 μm or more and 1.5 μm or less. By including the particle diameter within the above range, the oxide particles 101 make it easier for the network structure of the carbon nanotubes 20 described later to form a three-dimensional network structure. In addition, this increases the conductive paths of the carbon nanotubes 20, and the composite material 1 can easily obtain a low resistance value. For example, the film 10 may be laminated on the upper part of the substrate 2. For example, the oxide particles 101 include, but are not limited to, oxides containing any one or two or more elements of Li, Al, Fe, Ni, Co, Mn, Bi, La, Cu, Sn, Zn, V, Zr, Pb, Sm, Y, W, Si, P, Ru, Ti, Ge, Ca, Ga, Cr, Cd, Mg, Er. For example, the oxide particles 101 may include two or more oxides. For example, the oxide particles 101 are Zn 2-x TxP2O7 (T contains at least one element selected from Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, Zr, Nb, Mo, Ag, In, Sn, Sb, La, Ta, W, Bi, and satisfies 0 < x < 2. The oxide defined by the above chemical formula is a pyrophosphate. For example, the oxide particles 101 are Zn 2-z Mg z P2O7 (0 ≦ z ≦ 2) (hereinafter referred to as ZMPO) is included. ZMPO is included in the pyrophosphate. For example, the oxide particles 101 are Zn 2-z Mg z P2O7 (z = 0.4) is included. For example, the oxide particles 101 exhibit insulating properties. The oxide particles 101 containing ZMPO are insulating materials. For example, the film 10 may contain a silane coupling agent. By modifying the oxide particles 101 with the silane coupling agent, the adhesion of the carbon nanotubes 20 to the oxide particles 101 is improved. For example, the silane coupling agent is 3-aminopropyltriethoxysilane (APTES). For example, the carbon nanotube 20 may be a single-walled, double-walled, or multi-walled carbon nanotube. For example, the carbon nanotube 20 may be a semiconducting carbon nanotube. For example, the carbon nanotube 20 has a diameter of 0.7 nm to 1.5 nm. For example, the carbon nanotube 20 has a length of 100 nm to 1.5 μm. In the composite material 1 according to this embodiment, a plurality of carbon nanotubes 20 are dispersed in a film 10 formed by an assembly of oxide particles 101 so as to form a network on the surface of the oxide particles 101. The film 10 constitutes a network structure formed by a plurality of carbon nanotubes being entangled with each other. This network has a three-dimensional mesh structure.

[0015] (Composite material formation method) A method for forming the composite material according to the present embodiment will be described. The method for forming the composite material in this embodiment is carried out according to the flow shown in Fig. 2. Supplementary diagrams for each flow are also shown in Fig. 3 and Fig. 4.

[0016] First, an operator prepares a solution containing a silane coupling agent (ST1). For example, an operator prepares a solution X by dissolving a silane coupling agent in an ethanol solution. For example, the silane coupling agent is 3-aminopropyltriethoxysilane (APTES). For example, solution X contains APTES at a concentration of 0.5 wt %.

[0017] Next, the operator adds powder made of the oxide particles 101 to the solution containing the silane coupling agent to prepare a first suspension (ST2). For example, the powder contains oxide particles 101 having a particle diameter of at least 0.4 μm or more. The particle size of the oxide particles 101 contained in the first suspension 4 is the average particle size at D50 (particle size with a cumulative frequency of 50%) of the volume particle size distribution measured by laser light scattering. Therefore, when the particles of the raw material powder are aggregated, the particle size reflects the size of the aggregated particles, not the primary particle size, which is the particle size of a single particle. For example, the worker adds powder made of oxide particles 101 made of ZMPO to a solution containing a silane coupling agent. For example, the worker adds 1 g of powder made of ZMPO to 50 mL of the solution containing a silane coupling agent.

[0018] Next, the operator stirs the solution (first suspension 4) containing the silane coupling agent to which the powder has been added (ST3). For example, an operator stirs a solution containing a silane coupling agent and oxide particles 101 made of ZMPO for 6 hours in a room temperature environment.

[0019] Next, the worker washes the first suspension 4 with water, filters, and dries it (ST4). As a result, the worker can prepare a powder made of oxide particles 101 modified with a silane coupling agent. The adhesion of the carbon nanotubes 20 to the oxide particles 101 is improved by modification with the silane coupling agent.

[0020] Next, the operator prepares a second suspension 5 containing carbon nanotubes 20 (ST5). For example, the second suspension 5 may contain carbon nanotubes at a concentration of 0.0019 wt% to 0.0039 wt%. For example, the second suspension 5 may contain carbon nanotubes at a concentration of 0.0024 wt% to 0.0034 wt%. For example, the worker adds a surfactant to a dispersion medium and prepares a second suspension 5 in which the carbon nanotubes 20 are dispersed. The dispersion medium is not particularly limited as long as it is a solvent that can disperse and suspend the carbon nanotubes in ST7 described below, and examples that can be used include water, heavy water, an organic solvent, an ionic liquid, and mixtures of these. The worker can use a surfactant to thoroughly disperse the carbon nanotubes 20. The surfactant may be non-ionic. A non-ionic surfactant is easier to remove than an ionic surfactant. For example, the non-ionic surfactant may be a solution of polyoxyethylene alkyl ether such as polyoxyethylene (100) stearyl ether or polyoxyethylene (23) lauryl ether.

[0021] Next, the worker prepares a third suspension 6 containing the carbon nanotubes 20 and a powder of the oxide particles 101 (ST6). For example, the operator adds the powder of oxide particles 101 modified with a silane coupling agent prepared in ST4 to the second suspension 5. For example, the third suspension 6 may contain the oxide particles 101 at a ratio of 0.02 vol % to 0.25 vol %.

[0022] Next, the operator ultrasonically disperses the third suspension 6 prepared in ST6 (ST7).

[0023] Next, the worker treats the substrate 2 with a silane coupling agent (ST8). For example, the silane coupling agent used for the substrate 2 is APTES. The worker modifies the surface of the substrate 2 with an amino group by treating the substrate 2 with APTES. This improves the adhesion of the carbon nanotubes 20 to the substrate 2.

[0024] Next, the worker drops the third suspension liquid 6 onto the substrate 2 to form a film 10 (ST9). For example, the nozzle 7 is included in a dispenser, an inkjet, or the like. For example, the worker applies the third suspension 6, in which the carbon nanotubes 20 and the oxide particles 101a in powder are mixed, from the nozzle 7 onto the substrate 2. After that, the worker dries the substrate 2 at room temperature, and then dries the substrate 2 in an environment at 110°C for 2 hours. After drying, the worker washes the substrate 2 with water, and then bakes the substrate 2 in an environment at 180°C for 2 hours. Through these operations, a composite material 1 containing the oxide particles 101 is formed on the substrate 2. (Complete)

[0025] (Action and Effects) According to the composite material 1 of this embodiment, by containing oxide particles 101 in the film 10, which have a certain particle diameter relative to the length of the carbon nanotubes 20, the carbon nanotubes 20 can be attached so as to lean against the surface of the oxide particles 101, making it easier to arrange the carbon nanotubes 20 in three dimensions. Therefore, by arranging the carbon nanotubes 20 three-dimensionally, it becomes possible to form a film 10 having a thickness on the order of μm, and it becomes easy to form a three-dimensional network of CNTs. As described above, the composite material 1 according to the present disclosure easily forms a network of the carbon nanotubes 20.

[0026] Furthermore, in the composite material 1, the carbon nanotubes 20 can be easily arranged three-dimensionally, which increases the conductive paths of the carbon nanotubes 20 in the network structure. Therefore, the composite material 1 can easily obtain a low resistance value.

[0027] According to one embodiment of the present invention, the film 10 is formed of oxide particles 101 that have excellent adsorptivity for carbon nanotubes 20, and a carbon nanotube network is formed on the surface of the oxide particles 101. In addition, since the oxide particles 101 are an insulating material, the composite material 1 can easily form a network structure that utilizes the network properties of the carbon nanotubes 20 .

[0028] <Modification> In one example of the above-described embodiment, the worker created a third suspension 6 by adding oxide particles 101 to a second suspension 5 in which carbon nanotubes 20 are dispersed, but the worker may also add carbon nanotubes 20 to a suspension in which oxide particles 101 are dispersed.

[0029] Second Embodiment The first embodiment discloses a composite material 1 in which oxide particles 101 having a specific particle diameter are added to a network structure of carbon nanotubes 20 alone, thereby facilitating the formation of a three-dimensional network structure. In contrast, the bolometer according to this embodiment includes a light receiving unit that detects infrared rays and includes the composite material 1. The bolometer according to this embodiment also focuses on the fact that the composite material 1 can easily arrange the carbon nanotubes 20 three-dimensionally, thereby increasing the conductive paths of the carbon nanotubes 20 in the network structure and making it easier to obtain a low resistance value. Hereinafter, a bolometer 8 according to the present disclosure will be described as a second embodiment with reference to FIG.

[0030] (Bolometer configuration) The bolometer 8 comprises a composite material 1 , a base 99 , and an electrode 9 electrically connected to a carbon nanotube 20 . The bolometer 8 is used as a sensor for detecting infrared rays. The composite material 1 is an infrared receiving part. The composite material 1 is placed on a base 99 .

[0031] (Action and Effects) According to this embodiment, the composite material 1 provided in the bolometer 8 contains oxide particles 101 in the film 10, which have a particle diameter that is somewhat larger than the length of the carbon nanotubes 20, making it easier to arrange the carbon nanotubes 20 attached to the oxide particles 101 in a three-dimensional manner. Therefore, the bolometer 8 is likely to form a network of carbon nanotubes.

[0032] Furthermore, the composite material 1 included in the bolometer 8 can easily arrange the carbon nanotubes 20 three-dimensionally, which increases the conductive paths of the carbon nanotubes 20 in the network structure, and the composite material 1 can easily obtain a low resistance value. Therefore, the lower resistance value of the composite material 1 makes it easier to reduce the resistance value of the bolometer 8.

[0033] <Third embodiment> Hereinafter, as a third embodiment, an embodiment of a minimum configuration of a composite material according to the present disclosure will be described with reference to FIG.

[0034] (composition) The composite material 1b includes a film 10b containing oxide particles 101b having a particle diameter of at least 0.4 μm or more, and carbon nanotubes 20b forming a network on the surface of the oxide particles 101b.

[0035] (Action and Effects) According to this embodiment, the composite material 1b contains oxide particles 101b in the film 10b, which have a particle diameter that is somewhat larger than the length of the carbon nanotubes 20b, making it easier to arrange the carbon nanotubes 20b attached to the oxide particles 101b three-dimensionally. Therefore, a network of carbon nanotubes 20b is easily formed.

[0036] <Fourth embodiment> Hereinafter, as a fourth embodiment, an embodiment of a minimum configuration of a composite material forming method according to the present disclosure will be described with reference to FIG. The composite material forming method in this embodiment is carried out according to the flow shown in FIG.

[0037] The composite material forming method includes the steps of: preparing a solution containing a silane coupling agent (ST101); adding a powder of oxide particles to the solution containing the silane coupling agent to prepare a first suspension (ST102); preparing a second suspension containing carbon nanotubes (ST103); preparing a third suspension containing carbon nanotubes and the powder (ST104); and dropping the third suspension to form a film containing oxide particles having a particle diameter of at least 0.4 μm or more (ST105).

[0038] (Action and Effects) According to the composite material formation method of this embodiment, the composite material contains oxide particles in a film having a particle diameter that is relatively large relative to the length of the carbon nanotubes, making it easier to arrange the carbon nanotubes attached to the oxide particles in a three-dimensional manner. Therefore, the composite material forming method according to the present disclosure makes it easy to form a network of carbon nanotubes.

[0039] <Fifth embodiment> The first embodiment discloses a composite material 1 in which oxide particles 101 having a specific particle diameter are added to a network structure of carbon nanotubes 20 alone, thereby facilitating the formation of a three-dimensional network structure. In contrast, the composite material 1F according to this embodiment has a similar effect, but the composite material 1F is formed in a different manner, which makes it possible to suppress bundling of the carbon nanotubes 20. Hereinafter, a composite material 1F according to the present disclosure will be described as a fifth embodiment with reference to FIGS. In addition, components common to those disclosed above are given the same reference numerals and detailed explanations are omitted.

[0040] (Composition of composite materials) As shown in FIG. 11, a composite material 1F includes a porous film 10F, carbon nanotubes 20, and an insulating coating 30. For example, the composite material 1F has a temperature coefficient of resistance that exhibits a negative value. For example, the composite material 1F has a temperature coefficient of resistance whose absolute value is 2.5% / K or more, and the temperature coefficient of resistance in the composite material 1F is a value when the ambient temperature is changed from 25°C to 30°C. For example, composite material 1F has a sheet resistance of 250 MΩ or less at an ambient temperature of 25°C. The thickness of the composite material 1F can be appropriately set, and is, for example, 2 μm to 6 μm. The porous film 10F is a film containing oxide particles having a particle diameter of at least 0.4 μm or more. The porous film 10F includes oxide particles 101. For example, the porous membrane 10F may contain a silane coupling agent. For example, the porous film 10F may be laminated on top of the substrate 2.

[0041] In the following disclosure, the particle diameter of the oxide particles 101 is an average particle diameter. In the method for forming a composite material of the composite material 1F described below, the average particle diameter is preferably 0.8 μm or more and 1.5 μm or less. More preferably, it is 1.0 μm or more and 1.5 μm or less.

[0042] (Key points on composite material formation methods) The composite material 1F is formed by fixing oxide particles 101 on a substrate, and then impregnating the formed porous film 10F with a suspension containing carbon nanotubes. The method of impregnating the suspension includes a dipping method and a drop impregnation method. An example of the drop impregnation method is shown below. In one example of the drop impregnation method, oxide particles 101 are fixed on a substrate, and then a suspension containing carbon nanotubes 20 is dropped onto the substrate to impregnate the oxide particles 101.

[0043] (Overview of composite material formation methods) A method for forming the composite material according to the present embodiment will be described. The method for forming the composite material of the present embodiment is carried out according to the flow shown in Fig. 8. Supplementary diagrams for each flow are also shown in Fig. 9, Fig. 10, and Fig. 11. Note that ST103 may be replaced with ST101 or ST102 as appropriate.

[0044] First, an operator performs oxygen plasma processing on the substrate 2 (ST101). For example, an operator uses a silicon substrate covered with silicon oxide as the substrate 2, and removes organic matter and the like on the surface of the substrate 2 by oxygen plasma treatment.

[0045] Next, the worker treats the substrate 2 with a silane coupling agent (ST102). As a result, an adhesive layer 22 is formed on the substrate 2. For example, the silane coupling agent is 3-aminopropyltriethoxysilane (APTES).

[0046] Next, the worker prepares powder made of the oxide particles 101 in the same manner as in the first embodiment (ST103). In the present disclosure, the powder prepared in ST103 is a powder that is a material for producing a composite material 1F that includes oxide particles 101 made of ZMPO contained in a pyrophosphate salt described later and that includes a film containing oxide particles with a particle diameter of at least 0.4 μm or more.

[0047] Next, the operator prepares a suspension containing the oxide particles 101 (ST103A). For example, an operator ultrasonically disperses a solution (hereinafter also referred to as a "fourth suspension") in which the powder is added to pure water. For example, the fourth suspension may contain the oxide particles 101 in a ratio of 0.02 vol % to 0.25 vol %. Here, the ratio of the oxide particles 101 contained in the fourth suspension liquid is defined as the volume ratio of the added powder to the total volume of the pure water that is the material of the fourth suspension liquid and the added powder.

[0048] Next, the worker drops the suspension prepared in ST103A and dries it to form a porous film 10F containing oxide particles 101 (ST104). For example, in ST104, the worker may dry the substrate 2 at room temperature, and then dry the substrate 2 in an environment at 110° C. for 2 hours. The porous film 10F formed in ST104 has many pores in which the carbon nanotubes 20 can be arranged. The pores are formed between each of the aggregated oxide particles 101. By ST104, oxide particles 101 are fixed to the adhesion layer 22 on the surface of the substrate 2, as shown in FIG.

[0049] By dropping the suspension, the worker can layer the oxide particles 101 more easily than by applying the suspension.

[0050] Next, the worker performs oxygen plasma treatment on the dried oxide particles 101, and then treats them with a silane coupling agent after the oxygen plasma treatment (ST105). The oxygen plasma treatment can remove organic molecules that have adhered to the surfaces of the oxide particles 101 in the air, making it easier for the silane coupling agent to be uniformly adsorbed onto the dried oxide particles 101. For example, it is preferable that the worker performs the silane coupling treatment after fixing the oxide particles 101 to the substrate 2 via the adhesion layer 22 as in ST105. For example, the silane coupling agent used in ST105 is APTES. The worker modifies the surface of the oxide particle 101 with an amino group by treating the oxide particle 101 after the oxygen plasma treatment with APTES. This improves the adhesion of the carbon nanotube 20 to the oxide particle 101. In the method for forming the composite material 1F of the present disclosure, the worker does not need to modify the oxide particles 101 by silane coupling in advance.

[0051] Next, the worker drips a suspension containing carbon nanotubes (hereinafter also referred to as a "fifth suspension") onto the porous membrane 10F to impregnate the membrane (ST106). For example, the fifth suspension may include the carbon nanotubes 20 at a concentration of 0.0019 wt% to 0.0039 wt%. For example, the fifth suspension may include the carbon nanotubes 20 at a concentration of 0.0024 wt% to 0.0034 wt%. For example, the worker adds a surfactant to the dispersion medium and disperses the carbon nanotubes 20 therein to prepare a fifth suspension. The dispersion medium is not particularly limited as long as it is a solvent capable of dispersing and suspending the carbon nanotubes, and examples of the dispersion medium that can be used include water, heavy water, an organic solvent, an ionic liquid, and mixtures thereof. The surfactant may also be non-ionic, which is easier to remove than ionic surfactants. For example, the non-ionic surfactant may be a solution of polyoxyethylene alkyl ether such as polyoxyethylene (100) stearyl ether or polyoxyethylene (23) lauryl ether.

[0052] Next, the worker washes the substrate 2 on which the impregnated porous membrane 10F is laminated with water (ST108).

[0053] Next, the worker bakes the washed substrate 2 in an environment of 180° C. for 2 hours. In this manner, as shown in FIG. 10, the carbon nanotubes 20 are attached to the oxide particles 101, so that the carbon nanotubes 20 are arranged in the numerous pores of the porous film 10F.

[0054] Next, the worker forms an insulating film 30 on the baked substrate 2, and bakes it (ST110). In this manner, as shown in FIG. 11, the worker forms an insulating coating 30 on the porous film 10F in which the carbon nanotubes 20 are disposed. The insulating coating 30 is made of acrylic resin, epoxy resin, Teflon (registered trademark), etc. Examples include PMMA (poly methyl methacrylate), P4VP (poly(4-vinylpyridine)), and P4VBM (poly(4-vinylpyridine-co-bytyl methacrylate)). The porous membrane 10F is fixed by these resins. For example, the insulating coating 30 may include PMMA. In the present disclosure, an operator forms the insulating coating 30 by dropping a solution of PMMA (poly methyl methacrylate) dissolved in anisole and baking it. The worker bakes the substrate 2 after washing with water for 3 hours in an environment of 200° C. The worker heats the substrate 2 at 200° C. or higher to remove excess solvent, impurities, and the like. Through these operations, a composite material 1F containing oxide particles 101 is formed on the substrate 2. (Complete)

[0055] (Action and Effects) According to the composite material 1F of this embodiment, by containing oxide particles 101 having a certain particle diameter relative to the length of the carbon nanotubes 20 in the porous film 10F, the carbon nanotubes 20 can be attached so as to lean against the surface of the oxide particles 101, making it easier to arrange the carbon nanotubes 20 in three dimensions. Therefore, by arranging the carbon nanotubes 20 three-dimensionally, it becomes possible to form the porous film 10F having a thickness on the order of μm, and it becomes easy to form a three-dimensional network of CNTs. As described above, the composite material 1F according to the present disclosure easily forms a network of the carbon nanotubes 20.

[0056] Furthermore, in the composite material 1F, the carbon nanotubes 20 can be easily arranged three-dimensionally, which increases the conductive paths of the carbon nanotubes 20 in the network structure. Therefore, the composite material 1F can easily obtain a low resistance value.

[0057] Moreover, according to the composite material 1F of this embodiment, the porous film 10F formed of the oxide particles 101 having excellent adsorptivity for the carbon nanotubes 20 is present, and a carbon nanotube network is formed on the surface of the oxide particles 101. In addition, since the oxide particles 101 are an insulating material, the composite material 1F can easily form a network structure that utilizes the network properties of the carbon nanotubes 20.

[0058] Moreover, according to the composite material 1F of this embodiment, the step of forming the porous film 10F from the oxide particles 101 is performed before the carbon nanotubes 20 are attached to the oxide particles 101. This makes it possible to shorten the drying time of the fifth suspension dropped onto the porous membrane 10F, and to suppress bundling of the carbon nanotubes 20. In addition, after the carbon nanotubes are adsorbed onto the surfaces of the oxide particles 101 contained in the porous film 10F, excess carbon nanotubes can be removed by washing with water. As a result, as described later, a bolometer with a large absolute value of the temperature coefficient of resistance (TCR) can be realized. That is, the TCR is improved by suppressing the bundling of carbon nanotubes and removing excess carbon nanotubes.

[0059] <Modification of the Fifth Embodiment> Although the impregnation of the suspension containing carbon nanotubes is performed by a drop impregnation method as an example, a method based on immersion may also be used. For example, the formed porous membrane 10F may be impregnated by being immersed in a suspension containing carbon nanotubes. Then, the immersed porous membrane 10F is taken out and the water washing step of ST108 and subsequent steps are carried out.

[0060] Sixth Embodiment Hereinafter, as a sixth embodiment, an embodiment of a minimum configuration of a composite material forming method according to the present disclosure will be described with reference to FIG. The composite material forming method in this embodiment is carried out according to the flow shown in FIG.

[0061] The composite material forming method includes a step (ST1000) of forming a porous film containing oxide particles by dropping a suspension containing oxide particles having a particle diameter of at least 0.4 μm and drying, and a step (ST2000) of impregnating the porous film with a suspension containing carbon nanotubes.

[0062] (Action and Effects) According to the composite material formation method of this embodiment, the composite material contains oxide particles in a film having a particle diameter that is relatively large relative to the length of the carbon nanotubes, making it easier to arrange the carbon nanotubes attached to the oxide particles in a three-dimensional manner. Therefore, the composite material forming method according to the present disclosure makes it easy to form a network of carbon nanotubes.

[0063] Furthermore, according to the composite material forming method of this embodiment, the step of forming a porous film by dropping a suspension containing oxide particles and drying is performed before impregnating the porous film with a suspension containing carbon nanotubes. This means that the step of forming the porous film is carried out before the carbon nanotubes are attached to the oxide particles contained in the porous film. This makes it possible to suppress bundling of the carbon nanotubes 20. Furthermore, as will be described later, a bolometer with a large absolute value of TCR can be realized. EXAMPLES

[0064] The effects of the present disclosure will be described in more detail below with reference to examples. The conditions in the examples are examples of conditions adopted to confirm the feasibility and effects of the present disclosure, and the present disclosure is not limited to these examples. Various conditions may be adopted in the present disclosure as long as they do not deviate from the gist of the present disclosure and the purpose of the present disclosure is achieved.

[0065] FIG. 13 shows a plan view of the test element. Figure 13 is an enlarged view of the lower half of the element in row A, column R. Composite material 1 is formed in the channel part, and IV measurement is performed in the measurement part. There are eight measurement parts per test element. The size of the channel portion of the test element was 500 μm×100 μm, with an aspect ratio of 5:1. FIG. 14 shows a cross-sectional view of the test element. As shown in Figures 13 and 14, an insulating film (SiO2) was formed around the surface of the test element with a window that partially exposed the Ti / Au electrode. The insulating film was formed by sputtering.

[0066] Figure 15 shows the IV measurement results when the ambient temperature of the test element was 293 K. The test elements shown are the measurement results of two test elements in row A. Figure 16 shows the IV measurement results when the ambient temperature of the test element was 313 K. As with Figure 15, the measurement results of two test elements in row A are shown. 15 and 16, when the ambient environment of the test element rose from 293K to 313K, the value of Current (A) rose. In other words, it was confirmed that the temperature coefficient of resistance (TCR) shows a negative value, which means that the resistance value decreases as the ambient temperature of the test element rises. In this example, a negative TCR is shown because a semiconducting carbon nanotube is used. To calculate the TCR of the test element, measurements were performed using a semiconductor parameter analyzer. The test element was mounted on a ceramic carrier, placed in a cryostat, evacuated, and the TCR was measured while controlling the temperature.

[0067] FIG. 17 shows the relationship between the average resistance value and the TCR of the test element. For each element in the relationship shown in FIG. 17, the channel portion of the test element is a composite material of an oxide (ZMPO, BNFO, ZnO, Er2O3) and a carbon nanotube, or is a carbon nanotube. In the composite material of ZMPO and carbon nanotubes, the concentration of each suspension is adjusted when it is prepared. The solution containing the silane coupling agent contains APTES at a concentration of 0.5 wt%. Oxide particles 101 modified with the silane coupling agent are prepared from the first suspension 4, which is prepared by adding 1 g of ZMPO powder to 50 mL of the solution containing the silane coupling agent. The second suspension 5 contains carbon nanotubes at a concentration of 0.0029 wt%. The third suspension 6 contains the oxide particles 101 at a ratio of 0.2 vol%. The value of D50 (particle size at a cumulative frequency of 50%) of the volume particle size distribution measured by laser light scattering was used as the average particle size of the oxide particles 101 contained in the first suspension 4. The average particle size of the ZMPO in this example was 1.0 μm. Composites of other oxides (BNFO, ZnO, Er2O3) and carbon nanotubes were also prepared using a procedure similar to that for ZMPO. BNFO is BiNi1- y Fe y It is O3. (0 <y<1) The carbon nanotubes used in this example have a diameter of 1 nm and a length of 1 μm. The average thickness of each composite material is 5.2 μm for the composite material of ZMPO and carbon nanotubes, 4.3 μm for the composite material of BNFO and carbon nanotubes, 2.6 μm for the composite material of ZnO and carbon nanotubes, and 5.2 μm for the composite material of Er2O3 and carbon nanotubes.

[0068] Each element in Figure 17 was measured under three conditions: when the ambient temperature was raised from 25°C to 30°C, when the ambient temperature was raised from 20°C to 25°C, and when the ambient temperature was raised from 15°C to 20°C. Each value is the average of the values ​​measured at a total of 16 measurement points on the two test elements. The resistance value of each element was recorded as the average of the values ​​measured before the ambient temperature was raised. From FIG. 17, it was found that the composite material of ZMPO and carbon nanotubes has a negative TCR (absolute value 2.5% / K or more) with the same absolute value as that of carbon nanotubes alone. In addition, when comparing the resistance values, it was found that the composite material of ZMPO and carbon nanotubes has a lower resistance value than that of carbon nanotubes alone. It was confirmed that the composite material of ZMPO and carbon nanotubes has a sheet resistance of 30 MΩ or less at an ambient temperature of 20°C. The sheet resistance is obtained by multiplying the resistance value in FIG. 17 by the aspect ratio (×5). Since ZMPO is an insulating material, it is easy to form a network structure that makes use of the network characteristics of the carbon nanotubes 20, and it is believed that this has resulted in a TCR equivalent to that of carbon nanotubes alone. It is believed that the composite material of ZMPO and carbon nanotubes has a low resistance value because the conductive path of the carbon nanotubes 20 in the network structure is increased by the ZMPO containing a particle diameter of a specific size. It was found that the composite material of BNFO and carbon nanotubes has a negative TCR with a lower absolute value than the carbon nanotube alone. In addition, when comparing the resistance values, it was found that the composite material of BNFO and carbon nanotubes has a lower resistance value than the carbon nanotube alone. It is thought that the composite material of BNFO and carbon nanotubes achieves a low resistance value for the same reason as in the case of ZMPO. Fig. 18 shows the adhesion state of carbon nanotubes in a composite material of ZMPO and carbon nanotubes. From Fig. 18, it was confirmed that the composite material 1 is a film 10 including particles with a particle diameter of about 0.4 μm, particles with a particle diameter of about 0.5 μm, particles with a particle diameter of about 0.6 μm, particles with a particle diameter of about 0.7 μm, and particles with a particle diameter of about 1.2 μm. In this specification, the particle diameter of the oxide particle 101 is the maximum diameter of the general shape of a single particle or a group of particles that can be confirmed in a microscopic image obtained from an imaging device provided in an atomic force microscope (AFM), a scanning electron microscope (SEM), a transmission electron microscope (TEM), or the like. FIG. 19 shows the state of attachment of a single carbon nanotube. Fig. 20 shows the adhesion state of carbon nanotubes in a composite material of BNFO and carbon nanotubes. From Fig. 20, it was confirmed that the composite material 1 is a film 10 including particles with a particle diameter of about 0.4 μm, particles with a particle diameter of about 0.5 μm, particles with a particle diameter of about 0.6 μm, and particles with a particle diameter of about 0.7 μm. 17 to 20, it was confirmed that, compared to the adhesion state of carbon nanotubes alone, composite material 1 containing oxide particles 101 of a specific size facilitates the formation of a three-dimensional network structure.

[0069] 17, it was found that the composite material of ZnO and carbon nanotubes has a negative TCR (absolute value of 2.5% / K or more) with the same absolute value as the carbon nanotubes alone. In addition, when comparing the resistance values, it was found that the composite material of ZnO and carbon nanotubes has a slightly lower resistance value than the carbon nanotubes alone. Fig. 21 shows the adhesion state of carbon nanotubes in a composite material of ZnO and carbon nanotubes. From Fig. 21, it was confirmed that Composite Material 1 is a film containing particles with a particle diameter of about 0.4 μm or more and particles with a particle diameter of about 0.5 μm. 17 and 21, it was confirmed that, compared to the adhesion state of carbon nanotubes alone, Composite Material 1 contains ZnO of a specific size, which makes it easier to form a three-dimensional network structure. In Figure 17, it was found that the composite material of Er2O3 and carbon nanotubes has a negative TCR with a slightly lower absolute value than the carbon nanotubes alone. In addition, when comparing the resistance values, it was found that the composite material of Er2O3 and carbon nanotubes has a slightly higher resistance value than the carbon nanotubes alone. FIG. 22 shows the adhesion state of carbon nanotubes in a composite material of Er2O3 and carbon nanotubes. 17 to 22, it was found that the particle size of the oxide particles 101 of Er2O3 is smaller than that of other oxide particles. It was also confirmed that carbon nanotubes are less likely to adhere to Er2O3 than to carbon nanotubes alone. From these findings, it was considered that the composite material of Er2O3 and carbon nanotubes has a slightly higher resistance value than that of carbon nanotubes alone. EXAMPLES

[0070] In this example, a test element was produced by the composite material forming method of composite material 1F including ST101 to ST110.

[0071] FIG. 23 shows a side view of the test device. The configuration of the test element in Example 2 is as follows. Electrodes are formed on a silicon substrate covered with silicon oxide. A source electrode and a drain electrode are formed on one surface, and a gate electrode is formed on the other surface. The gate electrode is formed over the entire area of ​​the other surface. The source electrode is connected to GND (ground). On one surface, a porous film 10F and carbon nanotubes 20 are formed, and an insulating coating 30 is formed on the porous film 10F with the carbon nanotubes 20 disposed thereon. If the region where the insulating coating 30 is formed is referred to as region CO, the layered state in region CO is as shown in FIG. 11. In a region (region NE) adjacent to region CO, the carbon nanotubes 20 are removed by oxygen plasma treatment, and only the porous film 10F is formed. The layered state in region NE is as shown in FIG. 9.

[0072] In addition, a p-type silicon substrate was used as the silicon substrate. The source electrode and the drain electrode have a laminated structure in which a Au layer (90 nm) is laminated on a Ti layer (10 nm). The source electrode has a laminated structure in which a Au layer (200 nm) is laminated on a Ti layer (20 nm). The source electrode and the drain electrode were patterned by a lift-off method using photolithography.

[0073] The oxide particles 101 contained in the powder in this example had an average particle size of 1.3 μm. In the composite material of ZMPO and carbon nanotubes produced by the composite material forming method of composite material 1F, the concentration of each suspension was adjusted during production. In this example, the worker adjusted the oxide particles 101 in the fourth suspension to 0.1 vol %. In this example, the worker adjusted the carbon nanotubes 20 in the fifth suspension to 0.0029 wt %. In ST106, the operator drips the fifth suspension containing carbon nanotubes onto the porous membrane 10F to impregnate the same. After dripping, the operator holds the porous membrane 10F on which the fifth suspension has been dripped for a predetermined period of time. At this time, the amount of the fifth suspension is such that the porous membrane 10F is sufficiently soaked in the fifth suspension. In this embodiment, the operator held the dropped porous membrane 10F for 15 minutes. The composite material of ZMPO and carbon nanotubes produced by the composite material formation method of Composite Material 1F had an average thickness of 3.0 μm.

[0074] In this embodiment, the worker dripped a PMMA solution dissolved in anisole and baked the resulting film to form the insulating coating 30 on the porous film 10F having the carbon nanotubes 20 disposed thereon.

[0075] 24, the particle diameter of the oxide particles 101 was 0.5 μm or more. Note that, like the above-disclosed examples, the particle diameter of the oxide particles 101 in Example 2 is the maximum diameter of the general shape of a single particle or a particle group that can be confirmed in a microscopic image obtained from an imaging device equipped in an AFM, SEM, TEM, or the like. It was confirmed that the composite material of ZMPO and carbon nanotubes produced by the composite material formation method of composite material 1F had carbon nanotubes with smaller diameters than the carbon nanotubes shown in Figs. 18 to 22 of the above disclosed examples. This is believed to be because bundling of the carbon nanotubes 20 was suppressed by the composite material forming method of the composite material 1F.

[0076] FIG. 25 shows measurements taken as the ambient temperature is increased from 25° C. to 30° C. The measurement was performed by setting the drain voltage to −3 V and the gate voltage to 0 V with respect to the source electrode (GND) of the test element in Example 2.

[0077] It is considered that there is no significant difference in characteristics even if IV measurement is performed in the measurement section in a state where the composite material 1F is formed in the channel section of the test element in Example 1. In this Example 2, the gate voltage is fixed to suppress fluctuations in the gate voltage and to make the measured value more accurate.

[0078] It was found that the composite material of ZMPO and carbon nanotubes having the insulating coating 30 formed using a PMMA solution dissolved in anisole has a negative TCR (absolute value of 8.0% / K or more). It was confirmed that the absolute value of the TCR of the composite material of this example is even larger than the absolute value of the TCR shown in FIG. 17 of the example disclosed above. One of the reasons for this is believed to be that bundling of the carbon nanotubes 20 was suppressed by the composite material forming method of the composite material 1F. It is also possible that the insulating coating 30, which is formed using oxide particles or a PMMA solution dissolved in anisole, has a doping effect on the carbon nanotubes 20, and this is also thought to be one of the factors.

[0079] It was confirmed that the composite material of ZMPO and carbon nanotubes created by the composite material formation method of Composite Material 1F had a sheet resistance of 250 MΩ or less at an ambient temperature of 25°C. The sheet resistance was obtained by multiplying the resistance value in Figure 25 by the aspect ratio (x25). The size of the channel part of the test element in Example 2 was 500 μm x 20 μm, and the aspect ratio was 25:1.

[0080] From the above, it has been found that it is desirable for the oxide particles 101 to satisfy the following conditions. It is desirable that the maximum diameter of the estimated particle outline from the outline of a single particle or a group of particles obtained from a microscopic image is a certain particle diameter relative to the length of the carbon nanotube. For example, the oxide particle 101 has a particle diameter of at least 0.4 μm or more. It was confirmed that a network structure including particles of a specific size makes it easier to form a three-dimensional network structure compared to a network structure of single carbon nanotubes. It is also desirable that the absolute value of the TCR is 2.5% / K or more, and that the TCR is a value obtained when the ambient temperature is changed from 20°C to 25°C. Moreover, at an ambient temperature of 20° C., it is desirable for the composite material 1 to have a sheet resistance of 30 MΩ or less.

[0081] Although the embodiment of the present disclosure has been described above, this embodiment is shown as an example and is not intended to limit the scope of the disclosure. This embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the scope of the present disclosure. This embodiment and its modifications are included in the scope and gist of the present disclosure, as well as in the scope of the present disclosure and its equivalents.

[0082] A part or all of the above-described embodiments can be described as, but is not limited to, the following supplementary notes.

[0083] (Appendix 1) A film containing oxide particles having a particle diameter of at least 0.4 μm or more; Carbon nanotubes forming a network on the surface of the oxide particles; Includes Composite material.

[0084] (Appendix 2) The oxide particles contain at least pyrophosphate. 1. A composite material as described in Appendix 1.

[0085] (Appendix 3) The composition of the pyrophosphate is Zn 2-z Mg z P2O7(0≦z≦2) 2. A composite material as described in Appendix 2.

[0086] (Appendix 4) The composition of the pyrophosphate is Zn 2-z Mg z P2O7(z=0.4) 2. A composite material as described in Appendix 2.

[0087] (Appendix 5) The film contains a silane coupling agent. 5. The composite material of any one of claims 1 to 4.

[0088] (Appendix 6) It has a negative temperature coefficient of resistance. 5. The composite material of any one of claims 1 to 4.

[0089] (Appendix 7) The carbon nanotubes are semiconducting carbon nanotubes. 5. The composite material of any one of claims 1 to 4.

[0090] (Appendix 8) The absolute value of the temperature coefficient of resistance is 2.5% / K or more. The temperature coefficient of resistance is the value when the ambient temperature (environmental temperature) is changed from 20°C to 25°C. 5. The composite material of any one of claims 1 to 4.

[0091] (Appendix 9) At an ambient temperature of 20° C., the sheet resistance is 30 MΩ or less. 10. The composite material of claim 8.

[0092] (Appendix 10) A composite material according to any one of claims 1 to 4; a substrate having the composite material disposed thereon; an electrode electrically connected to the carbon nanotube; Equipped Bolometer.

[0093] (Appendix 11) preparing a solution containing a silane coupling agent; adding a powder of oxide particles to the solution to prepare a first suspension; forming a second suspension comprising carbon nanotubes; forming a third suspension containing the carbon nanotubes and the powder; Dropping the third suspension to form a film containing oxide particles having a particle diameter of at least 0.4 μm or more; Includes Composite material formation method.

[0094] (Appendix 12) In the second suspension, the carbon nanotube concentration is 0.0019 wt % to 0.0039 wt %; In the third suspension, the concentration of the oxide particles is from 0.02 vol % to 0.25 vol %. 12. The method of forming a composite material of claim 11.

[0095] (Appendix 13) A step of dropping a suspension containing oxide particles having a particle diameter of at least 0.4 μm or more and drying the suspension to form a porous film containing the oxide particles; impregnating the porous membrane with a suspension containing carbon nanotubes; Includes Composite material formation method.

[0096] (Appendix 14) In the impregnation step, the porous membrane is impregnated by dropping a suspension containing carbon nanotubes onto the porous membrane. 14. A method of forming a composite material as described in claim 13.

[0097] (Appendix 15) In the impregnating step, the porous membrane is impregnated by immersing it in a suspension containing carbon nanotubes; The immersed porous membrane is pulled up. 14. A method of forming a composite material as described in claim 13.

[0098] (Appendix 16) In the step of forming the porous film, The dried oxide particles are subjected to an oxygen plasma treatment, and then treated with a silane coupling agent after the oxygen plasma treatment. 16. A method of forming a composite material according to any one of claims 13 to 15. [Explanation of symbols]

[0099] 1 Composite materials 10 membrane 101 Oxide particles 101a Oxide particles in powder 2. Board 22 Adhesion layer 20 Carbon nanotubes 3. APTES Monolayer 4. First Suspension 5. Second Suspension 6. Third Suspension 7 Nozzles 8 Bolometer 9 electrodes 99 Foundation 1b Composite materials 1F Composite materials 10F porous membrane 30 Insulating Coating 10b membrane 101b Oxide particles 20b Carbon Nanotubes X Solution

Claims

1. A film containing oxide particles having a particle diameter of at least 0.4 μm or more; Carbon nanotubes forming a network on the surface of the oxide particles; Includes Composite material.

2. The oxide particles contain at least pyrophosphate.

2. The composite material of claim 1.

3. The composition of the pyrophosphate is Zn 2-x Mg x P 2 O 7 (0≦x≦2) 3. The composite material of claim 2.

4. It has a negative temperature coefficient of resistance. A composite material according to any one of claims 1 to 3.

5. A composite material according to any one of claims 1 to 3; a substrate having the composite material disposed thereon; an electrode electrically connected to the carbon nanotube; Equipped Bolometer.

6. preparing a solution containing a silane coupling agent; adding a powder of oxide particles to the solution to prepare a first suspension; forming a second suspension comprising carbon nanotubes; forming a third suspension containing the carbon nanotubes and the powder; Dropping the third suspension to form a film containing oxide particles having a particle diameter of at least 0.4 μm or more; Includes Composite material formation method.

7. In the second suspension, the carbon nanotube concentration is 0.0019 wt % to 0.0039 wt %; In the third suspension, the concentration of the oxide particles is from 0.02 vol % to 0.25 vol %.

7. A method for forming a composite material according to claim 6.

8. A step of dropping a suspension containing oxide particles having a particle diameter of at least 0.4 μm or more and drying the suspension to form a porous film containing the oxide particles; impregnating the porous membrane with a suspension containing carbon nanotubes; Includes Composite material formation method.

9. In the impregnation step, the porous membrane is impregnated by dropping a suspension containing carbon nanotubes onto the porous membrane.

9. A method for forming a composite material according to claim 8.

10. In the impregnating step, the porous membrane is impregnated by immersing it in a suspension containing carbon nanotubes; The immersed porous membrane is pulled up.

9. A method for forming a composite material according to claim 8.

Citation Information

Patent Citations

  • Bolometer material, infrared sensor, and manufacturing method thereof

    WO2021241575A1